Modulation of the crystallization of rapeseed oil using lipases and the impact on ice cream properties. (March 2023) - Monié, Aurélie; Habersetzer, Thomas; Sureau, Léa; David, Annabelle; Clemens, Karine; Malet-Martino, Myriam; Perez, Emile; Franceschi, Sophie; Balayssac, Stéphane; Delample, Mathieu
Graphical abstract: Highlights: Using different lipases modulate of the composition of rapeseed oil in polar lipids. Comparative kinetics of lipases were assessed directly by 13 C NMR. A presence of in-situ free fatty acids impacts the thermal behavior of liquid oils. Different crystallized rapeseed oils were directly used in ice cream production. Ice cream properties are positively correlated to the presence of polar lipids. Abstract: We investigated the possibility to use rapeseed as a main oil in ice cream formulations by changing its functionality when using different kinds of lipases. Through a 24 h-emulsification and a centrifugation, the modified oils were further used as functional ingredients. All lipolysis was first assessed as a function of time by 13 C NMR, where triglycerides consumption and the formation of low-molecular polar lipids (LMPL: monoacylglycerol and free fatty acids, FFAs) were selectively identified and compared. The more the FFAs, the sooner the crystallization (from −55 to −10 °C) and the later the melting temperatures (from −17 to 6 °C) measured by differential scanning calorimetry. These modifications were exploited in ice cream formulations with a significant impact on overall hardness (range of 60–216 N) and flowing during defrosting (from 1.29 to 0.35 g/min). The global behavior of products can be controlled by the composition of LMPL within oil.